A comparison of the influence of micro- and nano-silica on hydration kinetics of Portland cement under different temperatures. (10th July 2020) - Ma, Cong; He, Jionghuang; Qin, Tao; Long, Guangcheng; Du, Yinfei; Xie, Youjun
Highlights: Micro-silica has slight influence on hydration kinetics of cement at 20 °C and 40 °C. The effects of micro- and nano-silica on hydration kinetics are very similar under 50 °C and 60 °C. Nano-silica improves the phase boundary reaction at 60 °C. Abstract: Exothermic characteristics of Portland cement incorporating 1%wt micro- and nano-silica were researched by measuring the heat releases at different testing conditions. The presence of nano-SiO2 reduces the induction period, and this effect changes with temperature. The rising temperature makes silica fume generate more significant influence on the induction period. The maximal heat release rate is influenced slightly at normal temperature and decreased to some extent at elevated temperatures through replacing 1%wt cement by micro- and nano-silica. The effects of nano-SiO2 and silica fume at 60 °C are almost completely consistent with each other within 7 h of hydration including induction state, acceleration state and deceleration state. Silica fume presents the property of nano-SiO2 at high temperatures, which can also be observed by analyzing their cementitious indexes. The reaction kinetics of cement with nano-SiO2 and silica fume was analyzed by the classical Krstulović-Dabić model. The analysis results indicate that nano-SiO2 and silica fume can improve the hydration degrees ( α 1 and α 2 ) of the transformation from nucleation and crystal growth (NG) process to phase boundary reaction (I) process or I process to diffusion (D) process only at 60 °C. Nano-SiO2 can improve the phase boundary reaction at 50 °C and 60 °C judging by the difference between α 1 and α 2 . The possible mechanism of nano-SiO2 and silica fume influencing the hydration kinetics was also proposed.